Seaweed Dodol (Eucheuma Cottoni) Processing in UKM. Cahaya Madina Nunukan and Characteristics Products Produced in Nunukan Area (Borneo Engineering & Advanced Multidisciplinary International Journal, 2023)
From a biological point of view, seaweed is a primary producer producing organic matter and oxygen in the aquatic environment. From an economic standpoint, it is a potential commodity for development, given its nutritional value. Seaweed Dodol is a diversification of processed seaweed. Seaweed dodol is a type of food that belongs to the category of semi-wet food, which has low activity. The research method used is the direct practice of data collection and the results of observations carried out at UKM Cahaya Madina. In conclusion, the process of making dodol starts with preparing tools and materials, then washing the seaweed, cutting, blending, cooking, printing, dodol, drying and packaging. Seaweed dodol is a processed product that is very popular because of its soft texture, attractive colour, sweet taste and distinctive aroma.